The Role Talents Management in Consolidating Organizational Learning Process: An Applied Study at the Yemeni General Telecommunications Corporation (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This study aimed at accounting for the role of talents management in consolidating organizational learning process at the Yemeni General Corporation For telecommunication. To achieve the objective of the study, the researcher designed a questionnaire and administered it. The sample of the study consisted of (166) employees (General Manager, Manager and Department Head). They were selected randomly out of a total Population of (291) employees during the Year 2019. The descriptive analytic approach was used t reach conclusions.The finding of the study revealed existence of effect of talents management dimensions, all together and alone, (talents polarization, talents development, talents maintenance and managing talents, performance) in consolidating organizational process. The researcher recommended the leaders of the institution to practise talents organizational learning at the institution by supporting such behaviours and creating environment for talent employees.